(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper presents a predictive direct power control (DPC) of a three-phase neutral-point-clamped (NPC) converter in a wind power system based on a dual three-phase (DTP) permanent-magnet synchronous generator (PMSG). As the power in wind turbine systems increases, using a three-level NPC converter offers several advantages, including higher output power, reduced stress on semiconductor devices, and lower harmonic distortion in the output waveform, when compared to a conventional two-level converter. In the production system, a DTP PMSG is used. This generator is coupled with two three-phase, two-level voltage source converters, arranged in series to create a cascaded DC link. For interfacing with the electrical grid, the system utilizes a three-phase NPC converter. The proposed control technique uses two decoupled control loops: a field-oriented control FOC to achieve maximum power point tracking MPPT on the machine-side converters, and a finite control-set model predictive direct power control FCS-MPC-DPC for the NPC converter. The objectives include the tracking of active power, reactive power, and voltage balancing. The system's performance is evaluated through MATLAB/Simulink simulations.